Artikel Review : Sistem Penghantaran Obat Berbasis pH Tertarget pada Kolon: Tinjauan Mekanisme dan Efektivitas Formulasi Enterik - Nobel Pangarintungan (Indonesian Journal of Herbal and Biomedical Research, 2026)
pH-responsive drug delivery systems have emerged as a promising strategy to achieve targeted drug release in the colon by protecting drugs from premature release in the upper gastrointestinal tract. This review aimed to evaluate recent advances in pH-responsive colon-targeted drug delivery systems published between 2016 and 2025. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature was retrieved from PubMed, ScienceDirect, and SpringerLink using predefined keywords. After applying the inclusion and exclusion criteria, ten original research articles were included for qualitative synthesis. The findings demonstrated that pH-responsive nanoparticles, microparticles, and polymer-coated beads consistently minimized drug release under acidic conditions while enhancing drug release at colonic pH. Eudragit-based polymers, either alone or combined with natural polymers and advanced carrier materials, remained the most widely used formulations because of their favorable drug protection, encapsulation efficiency, controlled release, and therapeutic performance. Recent developments indicate a shift toward multifunctional and multi-responsive delivery platforms to improve colon-specific drug delivery. However, most available evidence is limited to preclinical studies, highlighting the need for further clinical investigations to facilitate future therapeutic applications.